Methodological procedure in the evaluation of projects using the cost-benefit analysis - Petrović, Dragana N.; Đedović, Branko N.; Petrović, Nikola Č. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Investment projects are complex business enterprises, which provide such a financial resourses and their realization takes a long time. Analyzing an investment idea and a large number of alternatives on the road to a final solution, requires a systematic approach and application of modern quantitive statistic and optimization methods in support to proper decisions. Flowchart of activities is given in the documents of pre-investment and investment studies, covering all phases of the project life cycle. Cost-benefit analysis provides strong support in evaluating project like a successful business venture and for evaluating project’s solution.  Indeed, this analysis is still rarely applied in our country, unlike of the practice in developed countries Methods and techniques of the cost-benefit analysis provide selection criterion of alternative solutions and strong quantitative predictions of flow business enterprise, optimize revenues and expenditures of initiator investments idea, which is strong support of correct decisions.  Cost- benefit analysis is the best done in the stage of pre-investment studies and later during the preparation of investment studies examine alternative solutions.
Keywords: Investment project; cost-benefit analysis; pre-investment studies; investment studies; life of the project; financial analysis; economic analysis.; alternative; solutions; projects; investments; enterprises